2018
DOI: 10.1177/0272431618797007
|View full text |Cite
|
Sign up to set email alerts
|

School Engagement and the Role of Peer Victimization, Depressive Symptoms, and Rumination

Abstract: The purpose of the current study was to explore the association between peer victimization and school engagement and the indirect effects of rumination and depressive symptoms in this association. Data on middle school students’ victimization experiences, school engagement, rumination, and depressive symptoms were collected from 887 sixth- through eighth-grade students utilizing self-report measures. Results indicated for both boys and girls a significant negative association between peer victimization and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
(123 reference statements)
3
9
0
2
Order By: Relevance
“…On the other hand, school connectedness, as a school ecosystem subsystem variable, can also mediate peer victimization and POGU. First of all, peer victimization is negatively associated with school connectedness, which is consistent with previous studies ( Wang et al, 2015 ; Dorio et al, 2019 ). It will be difficult for victimized adolescents to build trust with teachers and classmates, and due to less emotional support, warmth, and positive interaction in school, their level of school connectedness is low ( Buhs et al, 2006 ; Frojd et al, 2008 ; Garvik et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, school connectedness, as a school ecosystem subsystem variable, can also mediate peer victimization and POGU. First of all, peer victimization is negatively associated with school connectedness, which is consistent with previous studies ( Wang et al, 2015 ; Dorio et al, 2019 ). It will be difficult for victimized adolescents to build trust with teachers and classmates, and due to less emotional support, warmth, and positive interaction in school, their level of school connectedness is low ( Buhs et al, 2006 ; Frojd et al, 2008 ; Garvik et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…When adolescents are bullied by their peers, they may become less engaged in school activities because they perceive fewer emotionally supportive, warm, and positive interactions at school ( Halliday et al, 2021 ). Previous research has found that peer victimization is negatively correlated with school connectedness ( Wang et al, 2015 ; Dorio et al, 2019 ). In a longitudinal study, Ladd et al (2017) found that peer victimization can predict adolescents’ school participation and high-chronic victimization was consistently associated with lower school connectedness, academic self-perceptions, and academic achievement.…”
Section: Introductionmentioning
confidence: 92%
“…As it was expected (e.g. Dorio et al, 2018;Kotchick et al, 2020;Krause et al, 2018), constructs showed small, medium and large intercorrelations both concurrently and over time (r ranged from .17 to .58, p < .01).…”
Section: Descriptive Statistics Correlations and Mean Differencessupporting
confidence: 77%
“…Nesse sentido, foram encontrados 14 estudos que investigaram associações entre envolvimento em bullying e engajamento escolar, sendo que destes 12 eram empíricos (Buda & Szirmai, 2010;Cho & Choi, 2017;De Laet et al, 2015;Dorio et al, 2018;Iyer et al, 2010;Li et al, 2011;Mehta et al, 2013;Nakamoto & Schwartz, 2011;Perdue et al, 2009;Ripski & Gregory, 2009;Totura et al, 2014;Wang & Eccles, 2012) e dois teóricos ou de revisão de literatura (Herald-Brown et al, 2007;Juvonen, 2007). Estes estudos apontaram evidências de que o envolvimento em bullying está correlacionado negativamente com o engajamento escolar dos alunos.…”
Section: Envolvimento Em Bullying E Engajamento Escolarunclassified
“…Assim, de maneira geral, aponta-se que o bullying está negativamente correlacionado ao engajamento escolar, sendo que alunos que percebem ou se envolvem em situações de bullying apresentam menor engajamento escolar (Cho & Choi, 2017;Dorio et al, 2018;Iyer et al, 2010;Mehta et al, 2013;Perdue et al, 2009). Por outro lado, um bom relacionamento com pares está positivamente associado ao engajamento escolar, portanto, alunos que percebem aceitação e apoio por parte dos colegas tendem a apresentar maior engajamento escolar (Perdue et al, 2009).…”
Section: Envolvimento Em Bullying E Engajamento Escolarunclassified